The role of medical students in active search of transfusional incidents - Soares, Rodolfo Daniel de Almeida; Serafim, Daniel Soares; Leite, Emannuel Lucas de Sousa; Fernandes-Júnior, Francisco Ademar; Caldas, Gabriella Leonardo Oliveira; Rabello, Isabella Karen Freitas; Nunes, Karla Cristina Franco Guimarães; Barbosa, Lorena Caroline Vieira; Araújo, Manassés Medeiros Alves de (JOURNAL OF SURGICAL AND CLINICAL RESEARCH, 2017)
Purpose: The aim of this study was to report medical students' experience in hemovigilance through the active search of transfusion incidents. Methods: The study was done from January of 2013 to January 2016, at a university hospital. There were daily visits to all patients who had been transfused at least one blood component at this hospital, by using questionnaires about these transfusions. Transfusion incidents were identified, the cases were notified and passed on to doctors in order to confirm the adverse event. We analyzed, through active search, 12552 blood transfusions in 4255 transfused patients during the collection period. The average number of patients evaluated per student was 472 patients. Through hemotherapic and clinical knowledge, 67 transfusion incidents were identified, notified and confirmed, corresponding toan average of 7,44 per student. Knowing common aspects of blood transfusions and adverse events, as well as their prevention, allows safer hemotherapic technics. Conclusion: The present initiative improved doctor-patient relationship of the students, through daily contact and development of humanizing and ethics technics. It also enabled practical transfusional experience, contributing to an integral formation of the students.